IPTEK BAGI MASYARAKAT MESIN PENCACAH PELEPAH DAN DAUN KELAPA SAWIT UNTUK PAKAN SAPI DI DESA SEMPAN - Pristiansyah Pristiansyah; Hasdiansah Hasdiansah; Sugiyarto Sugiyarto (Jurnal Pengabdian Masyarakat Polmanbabel, 2021)
The growth and development of cattle is very dependent on the maintenance process, including the availability of feed in the surrounding environment, to meet the daily needs of cattle. In order for cow feed to be available and available, it is necessary to have a natural source of cow feed because it is easily available and has a high level of availability, namely in the natural surroundings. This natural source is in the form of grass or leaves that can be consumed directly by cattle, the availability of the feed is not influenced by weather conditions so that it can be obtained anytime and in large quantities. The grass that is available in the environment can be eaten directly by the cows, but the leaves must be processed first to make it easier for the cows to eat. For example, oil palm leaves and fronds, because the size of the palm fronds is quite large, so they cannot be directly used, it is necessary to have a chopping process so that they can be consumed by cows. Of course, the census process manually can be done but it is not effective, it requires a lot of time and a lot of effort. Based on these problems, it is necessary to mechanize the chopping process in order to simplify the process. The purpose of science and technology for the community in cattle breeder farmer groups in general is to increase the quality and capacity of production, especially cattle. Meanwhile, in particular, this IbM activity is expected to collaborate between partners and proposers from educational institutions. Partners can develop their business because they can meet the need for more animal feed through appropriate technology machines in the form of animal feed chopper machines, while institutions can apply science and technology directly and apply their knowledge into appropriate technology and can also introduce Polman educational institutions to the wider community.